Protein Pattern Analysis of Blood Globulin to Estimation of Genetic Distance among Population of Tegal, Magelang, and Mojosari Duck - Sadewo, AT (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2005)
The research to estimation gene frequency on the protein pattern on blood globulin and to estimation genetic distance among population Tegal, Magelang and Mojosari duck. The material were blood samples from 30 heads of duck. Electroforesis technique was used Sodium Dedocyl Sulfate (SDS) polyacrilamide cel elekctroforesis according to Deutcher (1990) method with instrument of polyacrilamide electroforesisÂ vertical system (Mini-protean II, Bio-Rad) was used for analysis protein of blood globulin. The gene frequency was estimated according to direct account method and tested for Hardy-Weinberg equilibrium, whereas the genetic distance was estimated by Nei (1972). Result the analysis of electroforesis showed that locus of globulin on the local duck population was controlled by three kind of gene. The gene frequency og GlbA GlbB and GlbC was about 0.05-0.50, migration distance was about 23-60 mm. The genetic distance among Tegal, Magelang and Mojosari duck as 0.010. result of the research was concluded that the protein pattern of blood globulin is usable to estimate both genetic distance and the relationship among population of Tegal, Magelang, and Mojosari duck and also it is estimated that the geographyc location represents a factor that influence the genetic distance. (Animal Production 7(3): 177-184 (2005)Â Key Words : Blood Globulin, Genetic Distance, Duck Population